Prevalence and effect of cardiac cachexia in advanced heart failure patients living in northern ireland. (29th July 2021) - Carson, M; Reid, J; Hill, L; Dixon, L; Donnelly, P; Slater, P; Hill, A; Fitzsimons, D
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Northern Ireland Chest Heart and Stroke Background/Introduction: Cardiac cachexia (CC) is a multifactorial wasting syndrome, resulting in significant weight loss and reduction in muscle mass. This is reflected in a detrimental effect on the patients' physical condition, quality of life and increases the patient's risk of premature death. Nonetheless, cardiac cachexia remains frequently unrecognised in clinical practice and therefore understudied. Purpose: To determine the prevalence and effect of cardiac cachexia in 200 patients with advanced heart failure (NYHA class III-IV) living in Northern Ireland. Methods: A mixed methods cross sectional study of patients recruited from a regional heart failure centre. A total of 200 patients with NYHA class III-IV heart failure were consented, enrolled and detailed data collected from their records. Anthropometric measures were taken (i.e. measures of lean muscle mass and fat tissue) and each individual completed three validated questionnaires - EQ-5D-5L (quality of life), FACIT-Fatigue and FAACT (various wellbeing subscales). Results: This population was predominately male (65.5%), with an average age of 74.4 years. Of the 200 NYHA class III-IV patients recruited, 30 were identified as cachectic (15%) Physically, cachectic patients were approximately 25 kg lighter than non-cachectic patients (p < 0.01) with an average BMI of 21.8 ± 4.4. The cachectic group showed significant reductions in mid-upper arm circumference (p < 0.01), skinfold thickness (p < 0.01) and upper arm fat area (p < 0.01), in comparison to the non-cachectic group. Measures of muscle mass were reduced, for example upper arm muscle circumference and area (p < 0.01), as well as grip strength (p < 0.01 for both right and left hands). Quality of life results from the EQ-5D-5L [see figure part b)] indicated an overall reduction for the cachectic group (p = 0.047). Of the EQ-5D-5L subscales, mobility and 'usual activities' were significantly reduced (p = 0.02 and p < 0.01 respectively), highlighting a significant change in the daily routine and ability of these patients. The FACIT-Fatigue questionnaire showed cachectic patients to be significantly more fatigued (p < 0.01) [see figure part a)], whilst the FAACT demonstrated reduced physical wellbeing (p = 0.02) and greater issues with diet and appetite (p < 0.01). Conclusions: This is the first prevalence study of cardiac cachexia within Northern Ireland. The 15% prevalence rate shows that the syndrome is relatively common in the advanced heart failure population. Cardiac Cachexia has severe physical consequences, attributed to an individual's weight loss in both fat and muscle tissue. Such changes may explain the subsequent decrease in mobility and the ability of these patients to conduct their 'usual activities'. Increased fatigue, reduced physical wellbeing and issues with diet and appetite only intensify these dire physical effects. It is hoped that these results will highlight the impact of this syndrome and promote targeted interventions.